New therapies targeting aging cells in the skin - Paszel-Jaworska, Anna; Gornowicz-Porowska, Justyna; Dańczak-Pazdrowska, Aleksandra; Polańska, Adriana; Krajka-Kuźniak, Violetta; Stawny, Maciej; Gostyńska, Aleksandra; Masternak, Michał; Rubiś, Błażej (Journal of Medical Science, 2023)
Senescence is accompanied by numerous processes that lead to alterations in cell metabolism, cell cycle arrest, and, increased production and secretion of senescence-associated secretory phenotype (SASP). Consequently, signaling pathways cascades are activated, leading to inflammation that can trigger multiple disorders, including cancer. Recently, a novel therapeutic approach was proposed based on targeting senescent cells using senolytics. This group of biologically active compounds includes fisetin, quercetin, dasatinib, and others. These compounds were shown to affect laboratory animals (rodents) by improving the quality of life and significantly increasing the length of life by reducing senescent cells pool in different organs. Based on these findings, we decided to evaluate the potential of these compounds in targeting senescent cells in human skin using in vitro model based on human-derived keratinocytes (HEKa) and fibroblasts (HDFa). Cytotoxicity assay revealed that the activity of the compounds was time- and dose-dependent as well as cell-type dependent. Further studies were performed to reveal the mechanistic aspect of these observations including assessment of the senescence marker, namely p16. However, it requires clarification before entering clinical trials to provide not only efficient but, first of all, safe application of senolytics to human skin.
Keywords: skin; senescence; aging; senolytics; fisetin; dasatinib; quercetin